RISIKO HUKUM BANK ATAS SERTIFIKAT TUMPANG TINDIH (OVERLAPPING) SEBAGAI AGUNAN PEMBIAYAAN HAK TANGGUNGAN - Balgis, Erna Rahma; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: The aim of this research is to examine banks' legal risks regarding overlapping certificates which are used as collateral for Mortgage financing. Overlapping certificates are a condition where two or more land ownership certificates are issued on the same land object. The main problem in this research is how is the bank's legal risk (mitigation) regarding overlapping certificates used as collateral for mortgage financing? The research method used is normative, the data used in this research is secondary data from the Statute Approach. The results of this research are that mitigating risks related to overlapping certificates used as collateral requires a comprehensive approach that includes verification, assessment and overall risk management. With the right steps, banks can protect themselves from potential losses arising from legal issues related to collateral until the process of binding Mortgage Rights can be carried out perfectly.Keywords: Legal Risk, Bank, Certificate,Overlapping